Building E-Learning Strategy and Developing E-Learning Action Plan in Higher Education - Polla, Gerardus (Bina Nusantara University, 2011)
Building an e-learning strategy and developing e-learning action plan requires two fundamental thing: first is adequate knowledge about what you want to accomplish, and the second is a willingness to articulate your plan in a meaningful way to all your stakeholders. Before the work begins, identify the key stakeholders who should participate in the strategy development. This paper intends to enlighten how to build an e-learning strategy in higher educations with some strategies that must be considered, such as defining who should participate; analyzing the current situation; setting visions; stating mission; analyzing gap; conducting force-field and SWOT analysis; creating strategy recomendations; and building an action plan. Additionally, this paper describes some steps for developing an e-learning action plan in higher education.